2017
DOI: 10.1080/15504263.2017.1319586
|View full text |Cite
|
Sign up to set email alerts
|

Housing First for Adults with Problematic Substance Use

Abstract: Adults who are homeless with problematic substance use can successfully be housed using a Housing First approach. However, further targeted services might be required to address other areas of functioning, such as health, substance use, and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 28 publications
2
73
0
1
Order By: Relevance
“…This finding occurred despite modest fidelity to the MISSION-Vet services in the GTO group. Among homeless individuals with co-occurring mental health and substance use in Permanent Supportive Housing, treatment engagement is an important first step in the recovery process, but individuals might need more time and longer term supports to address mental health and substance use [ 31 ]. Furthermore, others have also documented successful treatment engagement through the use of multifactorial treatment interventions like MISSION-Vet as well as the inclusion of the evidence based critical time intervention approach [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding occurred despite modest fidelity to the MISSION-Vet services in the GTO group. Among homeless individuals with co-occurring mental health and substance use in Permanent Supportive Housing, treatment engagement is an important first step in the recovery process, but individuals might need more time and longer term supports to address mental health and substance use [ 31 ]. Furthermore, others have also documented successful treatment engagement through the use of multifactorial treatment interventions like MISSION-Vet as well as the inclusion of the evidence based critical time intervention approach [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Substance abuse requires integrated, multidisciplinary care. Promoting stable housing through a "housing first" approach also seems to be crucial [ 43 , 44 ]. The results of this study also showed that older patients were more likely to receive DAA treatment than PEG-IFN–based regimens.…”
Section: Discussionmentioning
confidence: 99%
“…: unpublished data, 2020) identified 14 trials on permanent supportive housing (PSH). [30][31][32][33][34][35][36][37][38][39][40][41][42][43] Several trials across Canada and the United States showed that PSH initiatives house participants more rapidly compared with usual services (73 v. 220 d; adjusted absolute difference 146.4, 95% confidence interval [CI] 118.0 to 174.9); 30 increase the number of people who maintain stable housing at 2 years (pooled odds ratio [OR] 3.58, 95% CI 2.36 to 5.43); 30,40 and significantly increase the percentage of days spent stably housed. 41 No trials showed a sig nificant improvement in mental health symptoms compared with standard care.…”
Section: Evidence Summarymentioning
confidence: 99%
“…30,31,33,34,41,42 Two studies found that the mental health of PSH participants did not improve as much as that of usual care par ticipants (e.g., mean difference -0.49, 95% CI -0.85 to -0.12). 30,31 The At Home/Chez Soi trial showed small improvements in quality of life for high-needs (adjusted standardized mean difference 0.15, 95% CI 0.04 to 0.24) 30 and moderate-needs (mean difference 4.37, 95% CI 1.60 to 7.14) homeless participants in patients receiving PSH. 41 Youth receiving PSH saw larger improvements in their quality of life during the first 6 months (mean difference 9.30, 95% CI 1.35 to 17.24), which diminished over time (mean difference 7.29, 95% CI -1.61 to 16.18).…”
Section: Evidence Summarymentioning
confidence: 99%